Advancing Relevance, Credibility, Legitimacy, and Effectiveness as a Heuristic for Local-Parallel Scenarios - Cradock-Henry, Nicholas A.; Frame, Bob (Frontiers in Climate, 2021)
The parallel scenario process provides a framework for developing plausible scenarios of future conditions. Combining greenhouse gas emissions, social and economic trends, and policy responses, it enables researchers and policy makers to consider global-scale interactions, impacts and implications of climate change. Increasingly, researchers are developing extended scenarios, based on this framework, and incorporating them into adaptation planning and decision-making processes at the local level. To enable the identification of possible impacts and assess vulnerability, these local-parallel scenarios must successfully accommodate diverse knowledge systems, multiple values and competing priorities including both ‘top down’ modelling and ‘bottom-up’ participatory processes. They must link across scales, to account for the ways in which global changes affect and influence decision-making in local places. Due to the growing use of scenarios, there is value in assessing these developments using criteria or, more specifically, heuristics that may be implicitly acknowledged rather than formally monitored and evaluated. In this Perspective, we reflect on various contributions regarding the value of heuristics and propose the adoption of current definitions for Relevance, Credibility and Legitimacy for guiding local scenario development as the most useful as well as using Effectiveness for evaluation purposes. We summarise the internal trade-offs (personal time, clarity-complexity, speed-quality, push-pull) and the external stressors (equity and the role of science in society) that influence the extent to which heuristics are used as ‘rules of thumb’, rather than formal assessment. These heuristics may help refine the process of extending the parallel scenario framework to the local and enable cross-case comparisons.